Impact of heat stress on growth and physiological parameters of soybean varieties at the seedling stage - Bashir Hassan; Samanhudi; Parjanto; Setyawati Andriyana; Komariah; Senge Masateru; Rahayu Muji; Salma Fathin Tilmiidzah (BIO Web of Conferences)
Climate change-induced heat stress poses a significant threat to global soybean production. This study investigated the impact of heat stress on growth and physiological parameters of 18 Indonesian soybean varieties at the seedling stage. Treatments involved exposing two-week-old seedlings to temperatures 25, 30, 35, 40 and 45°C for four hours daily over four consecutive days. The parameters assessed were survival rate, root length, shoot length, total plant weight, and relative water content. Results revealed significant variability in heat stress tolerance among varieties. While all varieties showed optimal growth at 25°C, increasing temperatures from 25 to 30°C led to an increase in growth. A critical threshold was observed between 35 and 40°C, where most varieties experienced a sharp performance decline. Notably, varieties Demas 1, Gepak Kuning, and Agromulyo consistently outperformed others even at 45°C where all other couldn’t survive, maintaining higher survival rates and better growth parameters even under severe stress conditions. This study provides valuable insights into soybean heat stress tolerance mechanisms and identifies promising genetic resources for breeding heat-resilient cultivars in Indonesia. Our findings contribute to the development of strategies to mitigate the impacts of climate change on soybean production, crucial for ensuring global food security in the face of rising temperatures.